Before It’s Too Late : Deriving Sustainable Value from Wildlife in the Western Congo Basin - World Bank (World Bank, Washington, DC, 2018)
The Western Congo Basin (WCB) defined here as comprising Cameroon, the Central African Republic, Gabon, and the Republic of Congo is being rapidly emptied of its wild animals, with alarming rates of poaching in all four countries. High levels of poaching have numerous deleterious effects for sustainable development. In the WCB, efforts to protect wildlife have focused heavily on the establishment and management of protected areas, often within the context of a landscape-based approach that attempts to engage nearby communities and other land users. The low perceived value of forest wildlife resources for local communities is partially attributable to a lack of economic opportunities currently derivable from the sustainable management of wildlife assets. In a bid to help the WCB countries address this downward spiral, this study identifies approaches that can enhance the economic value of wildlife resources for local communities and governments as a contribution to poverty reduction, economic development, and conservation. It aims to do so at the regional and national levels as a single country cannot address this crisis given the fluidity of both borders and wildlife in the region. Naturally, the set and sequence of solutions most appropriate in any given setting will depend on a number of country-specific conditions. Nevertheless, the majority of the recommendations in this report apply to all four WCB countries. In that spirit, the study first provides an overview of the poaching crisis, using elephants as a case study to illustrate the scale of the problem (chapter 2). It then proceeds to analyze who the poachers are (chapter 3) to better understand drivers of poaching, while Chapter 4 analyzes the policy framework. Chapter 5 proposes approaches for creating economic value from wildlife, sharing it with communities, and creating the necessary underlying governance conditions, providing best-practice examples from other parts of the world. Chapter 6 presents conclusions.